Dynamic Group data sharing framework on Cloud Servers - Mallesh Goud; Pratika Malya (Macaw International Journal of Advanced Research in Computer Science and Engineering, 2015)
In this paper, we proposed a secured multi-owner data sharing scheme for a dynamic group in people, in general, cloud. By furnishing AES encryption with Convergent key while transferring the information, any cloud client can safely impart information to others. In the meantime, the capacity overhead and encryption calculation expense of the plan are free with the quantity of repudiated clients. Also, I break down the security of this plan with thorough confirmations. One-Time Secret word is one of the simplest and most well-known types of confirmation that can be utilized for securing access to accounts. One-Time Passwords are frequently alluded to as secure and more grounded types of confirmation in a multi-owner manner. Broad security and execution examination demonstrates that our proposed plan is profoundly productive and fulfills the security necessities for open cloud-based secure group sharing.